Influencia de la temperatura y el tiempo de reacción en la hidroisomerización de diésel renovable (2016)
The production of biofuels from vegetable oils and/or animal fats has experienced great growth in the last two decades. The procurement of biofuels with properties similar to fossil fuels, is a challenge due to the technical requirements in quality especially in the properties of fluidity in the cold. The hydroisomerization of n-paraffinic compounds is the most viable way to meet this objective. In this study a real load of renewable diesel obtained via the coprocessing of an ordinary fossil (DMO) with vegetable oils was used. The catalytic tests were carried out in an autoclave with mixing, using a commercial hydrocracking catalyst. The reaction was evaluated at 5.5 MPa, at a temperature range from 320°C to 350°C, and a time range from 2 to 5 h. The results show the procurement of a product with an improved fluidity point until 0°C, this being the best result. Furthermore the performance of both cuts bionafta and biojet increase in the established operating conditions (2 h of reaction, 320ºC, 5,5 MPa), an appreciable reduction in liquid performance of products for reaction times greater than 2 h and temperatures above 320°C was also observed.